Rifaximin for the prevention of spontaneous bacterial peritonitis and hepatorenal syndrome in cirrhosis: a systematic review and meta-analysis. Issue 10 (October 2017) - Kamal, Faisal; Khan, Muhammad Ali; Khan, Zubair; Cholankeril, George; Hammad, Tariq A.; Lee, Wade M.; Ahmed, Aijaz; Waters, Bradford; Howden, Colin W.; Nair, Satheesh; Satapathy, Sanjaya K.
Abstract : Prophylactic antibiotics have been recommended in patients with a previous history of spontaneous bacterial peritonitis (SBP). Recently, there has been interest in the use of rifaximin for the prevention of SBP and hepatorenal syndrome (HRS). We conducted a meta-analysis to evaluate this association of rifaximin. We searched several databases from inception through 24 January 2017, to identify comparative studies evaluating the effect of rifaximin on the occurrence of SBP and HRS. We performed predetermined subgroup analyses based on the type of control group, design of the study, and type of prophylaxis. Pooled odds ratios (ORs) were calculated using a random effects model. We included 13 studies with 1703 patients in the meta-analysis of SBP prevention. Pooled OR [95% confidence interval (CI)] was 0.40 (95% CI: 0.22–0.73) ( I 2 =58%). On sensitivity analysis, adjusted OR was 0.29 (95% CI: 0.20–0.44) ( I 2 =0%). The results of the subgroup analysis based on type of control was as follows: in the quinolone group, pooled OR was 0.42 (95% CI: 0.14–1.25) ( I 2 =55%), and in the no antibiotic group, pooled OR was 0.40 (95% CI: 0.18–0.86) ( I 2 =64%). However, with sensitivity analysis, benefit of rifaximin was demonstrable; pooled ORs were 0.32 (95% CI: 0.17–0.63) ( I 2 =0%) and 0.28 (95% CI: 0.17–0.45) ( I 2 =0%) for the comparison with quinolones and no antibiotics, respectively. Pooled OR based on randomized controlled trials was 0.41 (95% CI: 0.22–0.75) ( I 2 =13%). For the prevention of HRS, the pooled OR was 0.25 (95% CI: 0.13–0.50) ( I 2 =0%). Rifaximin has a protective effect against the development of SBP in cirrhosis. However, the quality of the evidence as per the GRADE framework was very low. Rifaximin appeared effective for the prevention of HRS.